1975
DOI: 10.1182/blood.v46.2.209.bloodjournal462209
|View full text |Cite
|
Sign up to set email alerts
|

Platelet storage at 22 degrees C: role of gas transport across plastic containers in maintenance of viability

Abstract: Containers constructed of polyvinylchloride (PVC) are used for the storage of platelet concentrates (PC) for transfusion, At 22 degrees C, pH often falls to such low levels (pH is less that 6.0) that viability is lost. Far lesser degrees of pH fall are observed in bags constructed of polyethylene (PE). In this study, pH, PO2, PCO2, platelet count, lactate concentration, microscopic morphology, and viability after 51- chromium labeling were evaluated during storage at 22 degrees C under a variety of circumstanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
110
1
3

Year Published

1976
1976
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(126 citation statements)
references
References 12 publications
12
110
1
3
Order By: Relevance
“…The platelets were stored under standard conditions. Platelet count, MPV and PF4 content in the control PCs remained constant during storage, while the evolutions in lactate and pH were in concert with data from other studies (Murphy & Gardner, 1975: Taylor et al, 1983Kilkson et al, 1984). The changes in platelet count, MPV and PF4 content after UV irradiation both at doses of 4 and 8 J/cm2 were indicative for platelet activation and reached significance compared to age-matched controls after 72 or 96 h of storage.…”
Section: Biochemical Analysis Of Platelet Concentratessupporting
confidence: 83%
See 1 more Smart Citation
“…The platelets were stored under standard conditions. Platelet count, MPV and PF4 content in the control PCs remained constant during storage, while the evolutions in lactate and pH were in concert with data from other studies (Murphy & Gardner, 1975: Taylor et al, 1983Kilkson et al, 1984). The changes in platelet count, MPV and PF4 content after UV irradiation both at doses of 4 and 8 J/cm2 were indicative for platelet activation and reached significance compared to age-matched controls after 72 or 96 h of storage.…”
Section: Biochemical Analysis Of Platelet Concentratessupporting
confidence: 83%
“…In contrast, PCs exposed to 8 J/cm2 resulted in poor recoveries 1 h and 1 6 h after transfusion. The difference in post-transfusion recovery between the two doses of UVB is not explained by a decrease in pH (Murphy & Gardner, 1975), since pH values of PCs exposed to 8 J/cm2 remained above 6.5 during the first 48 h of storage (Table I). Several studies (Rinder et al, 1991b;Triulci et al, 1991) have demonstrated that an increased expression of P-selectin on the platelet membrane is correlated with decreased post-transfusion recoveries.…”
Section: Discussionmentioning
confidence: 93%
“…In a plasma volume of 20 nll, pH was found to drop below 6.0 after 7 2 h storage, seriously impairing platelet viability. Since pH is inversely related to platelet concentration (Murphy & Gardner, 1975), a pH greater than 6.0 can be maintained by decreasing the platelet concentration to less than 1.7x 1o12/l. (Fig I).…”
Section: Anticoagulantmentioning
confidence: 78%
“…Tests that do correlate with viability, as shown by some, but not all, investigators, include the morphology score (percentage of platelets that are discoid or spheroid), the hypotonic shock response (HSR), extent of shape change (ESC) and platelet adenosine triphosphate (ATP) levels (Slichter, 1981;Holme, 1998 (Murphy et al, 1970;Slichter & Harker, 1976;Murphy, 1985), but the relationship between high pH and viability is less clear. Murphy & Gardner (1975) showed loss of recovery in vivo at pH values above 7Á2 but no relationship between viability and pH between 6Á0 and 7Á2. Poor recovery has also been associated with pH values of around 7Á7 .…”
mentioning
confidence: 89%